Immunological differences between insect venom‐allergic patients with and without immunotherapy and asymptomatically sensitized subjects. Issue 6 (19th December 2017) - Arzt, L.; Bokanovic, D.; Schrautzer, C.; Laipold, K.; Möbs, C.; Pfützner, W.; Herzog, S. A.; Vollmann, J.; Reider, N.; Bohle, B.; Aberer, W.; Sturm, G. J.
Abstract: Background: Currently available tests are unable to distinguish between asymptomatic sensitization and clinically relevant Hymenoptera venom allergy. A reliable serological marker to monitor venom immunotherapy (VIT) does also not exist. Our aim was to find reliable serological markers to predict tolerance to bee and vespid stings. Methods: We included 77 asymptomatically sensitized subjects, 85 allergic patients with acute systemic sting reactions, and 61 allergic patients currently treated with VIT. Levels of sIgE and sIgG4 to bee and vespid venom, rApi m 1, and rVes v 5 were measured immediately after allergic sting reactions or before sting challenges and 4 weeks later. All sting challenges were tolerated. The inhibitory activity was determined using BAT inhibition and ELIFAB assay. Results: Median sIgG4 levels were 96‐fold higher in VIT patients ( P < .001) while sIgE/sIgG4 ratios were consistently lower ( P < .001). The ELIFAB assay was paralleled by low sIgE/sIgG4 ratios in VIT patients, showing markedly higher allergen‐blocking capacity ( P < .001). An almost complete inhibition of the basophil response was seen in all patients treated with vespid venom, but not in those treated with bee venom. Four weeks after the sting, sIgE and sIgG4 levels were increased in allergic and asymptomatically sensitized patients, but not in VIT patients. Conclusion: Immunological responses after stings varied in bee and vespid venom‐allergic patients. In patients under VIT, sIgE and sIgG4 remained completely stable after sting challenges. Monitoring VIT efficacy was only possible in vespid venom allergy, and the sIgG4 threshold for rVes v 5 had the highest sensitivity to confirm tolerance. The BAT inhibition test was the most reliable tool to confirm tolerance on an individual basis.